Synthesis of the AB ring system of clifednamide utilizing Claisen rearrangement and Diels–Alder reaction as key steps. Issue 3 (24th November 2015) - Loke, Inga; Bentzinger, Guillaume; Holz, Julia; Raja, Aruna; Bhasin, Aman; Sasse, Florenz; Köhn, Andreas; Schobert, Rainer; Laschat, Sabine
Abstract : A synthesis to the functionalized AB ring system of clifednamide, member of macrocyclic tetramic acid lactams, was developed involving an Ireland–Claisen rearrangement and an intramolecular Diels–Alder reaction. Abstract : In order to construct the functionalized AB ring system of clifednamide, member of the class of macrocyclic tetramic acid lactams, a synthesis was developed which utilized an Ireland–Claisen rearrangement and an intramolecular Diels–Alder reaction. Starting from di- O -isopropylidene-d -mannitol the allyl carboxylate precursor for the sigmatropic rearrangement was prepared. This rearrangement proceeded diastereoselectively only in the presence of an allyl silyl ether instead of the parent enone in the side chain, as suggested by deuteration experiments. A subsequent Diels–Alder reaction yielded the target ethyl hexahydro-1 H -indene-carboxylate with high diastereoselectivity. Quantum-chemical investigations of this intramolecular Diels–Alder reaction support the proposed configuration of the final product.